New Office Supports Maine Climate Action - Gassett, Parker; Fernandez, Ivan (Maine Policy Review, 2023)
Expanding and expediting access to climate change information can improve collective action outcomes. Accordingly, the Maine Climate Action Plan called for the creation of an information-coordinating hub, to enable effective and efficient use of climate information in Maine’s climate change response. To aid that need, the University of Maine created the Maine Climate Science Information Exchange (MCSIE) office as a gateway to information about climate-relevant research, the scientists conducting that research, and the most recent data and applied science efforts relating to Maine’s climate change strategies. The office was established in 2023, after a year of developing prototypes of the functions of information coordination and investigating how universities in other states are or are not involved in implementing each state’s climate action plan.
Keywords: Climate change; Forest Sciences; Forest Products; Agriculture; Food Systems; Marine; Coastal Communities